Orders of Power Growth near the Critical Strip of the Riemann Zeta Function - Makarov, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study the asymptotic behavior of the functions ζ(z) and ζ−1(z) near the line x = 1.